Maintaining an empowered school community: Introducing digital technologies by building digital literacies at Beehive Montessori School (UCL Press, 2020)
In 2019, educators at Beehive Montessori School (Beehive) in Western Australia implemented their self-defined digital literacies framework. The framework guided their approach to, and use of, digital technologies in their classrooms. Doing so came out of a whole school action research project in which the school became a hub for inquiry and educators, and researchers worked together to identify issues and develop improvement processes. At the project conclusion, the educators and researchers had collaboratively defined a solution that met the mandated curriculum needs and fitted with the school autonomy. Most importantly the project and the solution empowered educators, as it aligned with the school-identified virtues and utilized the three-period lesson to teach it, all of which was consistent with Montessori pedagogy.